Finding motivational factors for working with the police as an important tool for personnel stabilization of the security corps - Bajura, Jan; Habich, Lukáš; Najman, Tomáš; Víšek, Jiří (Revista Administração em Diálogo - RAD, 2025)
The selection and especially the stabilization of personnel capital should be a key area of interest for all senior managers of security forces. The motivation of police officers is a key element for the efficient and professional performance of their work. One of the most important functional elements of the organization is a quality analysis of the process of acquiring new employees. Given that the Police of the Czech Republic has been dealing with the problem of replenishing the staff for a long time, this contribution is focused on the motivational factors of members of the Police of the Czech Republic, which have a significant effect on personnel stability and also on properly targeted personnel recruitment. The article presents the results of a research investigation in which police officers from the Czech Republic and the Slovak Republic participated.